Coral reef condition Kepala Jeri Island, Batam, Riau Islands, Indonesia - AUNURRAHMAN AUNURRAHMAN; SUTRISNO ANGGORO; SURADI WIJAYA SAPUTRA; MAX RUDOLF MUSKANANFOLA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Aunurrahman, Anggoro S, Saputra SW, Muskananfola MR. 2024. Coral reef condition Kepala Jeri Island, Batam, Riau Islands, Indonesia. Biodiversitas 25: 2820-2827. Understanding the actual condition of vulnerable coral reef ecosystems such as Kepala Jeri Island (Indonesia) is critical to enabling appropriate management planning. This research aimed to identify current coverage, observe the condition of the coral ecosystem, and identify the species composition of coral reefs in Kepala Jeri Waters. Data collection includes the spatial distribution, actual condition, and species composition of the coral ecosystem on Kepala Jeri Island, Riau Islands, Indonesia. Using an algorithm-based classification, we analyzed the spatial distribution of coral reefs from Landsat 8 OLI imagery. The study used Landsat OLI 8 images from the US Geological Survey (USGS) and observed the data using a line intercept transect. We obtained the actual coral conditions and species composition through field observation. The results revealed a total distribution of 239.67 ha of coral reef ecosystem in the surrounding area of Kepala Jeri Island. Unfortunately, the coral reef on Kepala Jeri Island was in poor condition, with an approximate living coral coverage of only 5-29.33%. Compared to other locations, we found the sand cover to be the highest, ranging from 28.33 to 51.67%. We also found that the seagrass bed had invaded the coral ecosystem, suggesting a reduced or absent population of halos grazers. Only the western and northern sides of Kepala Jeri Island exhibit adequate coral diversity despite discovering 26 coral species. Even though 26 coral species were found on Kepala Jeri Island, only the western and northern sides have adequate coral diversity. The findings suggest that the coral reef ecosystem on Kepala Jeri Island is under severe degradation, while the risk of further degradation remains. Therefore, human intervention is absolutely important to improve the coral reef ecosystem on Kepala Jeri Island, ensuring its sustainability.